ADSORPTION OF Ni, Mo AND BINARY SOLUTIONS FROM CHITOSAN SPHERES (International Journal of Engineering Sciences & Management Research, 2018)
In this work, chitosan gel beads (spheres) were prepared using a phase inversion method. They were used to study the process of sorption of nickel and molybdenum ions in aqueous solutions by means of equilibrium analysis and sorption kinetics. The results obtained establish that both metals as a function of the variation of the concentration, obey the Freundlich model with values of load capacity of 2.49 mg g-1 for Ni and 41.84 mg g-1 for Mo. The sorptionresults of the Ni (II), Mo (VI) and Ni (II) / Mo (VI) mixtures with chitosan beads showed that both ions are extracted, obtaining extraction percentages of 36.64% for Ni (II) and 68.9% for Mo (VI). For the case of the mixture, a percentage of 74.22% is reported. This result, which is shown above the values of individual extraction, yields a synergistic process. Obtaining the most efficient extraction for the Mo (VI) in simple system, this is ratified with the capacity value (qm) obtained from the Freundlich model.